Influence of drilling process parameters on hybrid vinyl ester composite. Issue 12 (10th September 2018) - Anand, G.; Alagumurthi, N.; Palanikumar, K.; Venkateshwaran, N.; Elansezhain, R.
ABSTRACT: In the modern world, the use of hybrid composite becomes unavoidable. They have their unique and tailor-made properties which makes them suitable for many engineering and industrial applications. But the restriction on the use of composites arises during machining of these composites. Unlike conventional materials, machining of composites is a tedious process due to their anisotropic nature. In the current research work, the prepared high strength hybrid composite is subjected to one of the important machining process say drilling and the process parameters are optimized for the multiple output characteristics namely delamination, torque and thrust force. Taguchi technique aided with grey relational analysis is used for optimization purpose. From the experimental outcome, it is clear that the machining characteristics can be improved at optimum machining conditions. And it is also found that the diameter of the drill has the major effect on the output characteristics.